Projeto terapêutico singular: perspectivas de usuários e profissionais de um Centro de Atenção Psicossocial - Zubiaurre, Priscila de Melo (2024)
In the scenario after the Brazilian Psychiatric Reform, the Singular Therapeutic Project is characterized as an important care strategy in Psychosocial Care Centers, as it prioritizes reception, the formation of a bond between user-service and co-responsibility between the people involved in the act of care . On the other hand, it is known that there are weaknesses in understanding the instrument, which may imply sharing care, co-responsibility and co-management of the instrument. The general objective of this research is to analyze the actions of the Singular Therapeutic Project in a Psychosocial Care Center in relation to the intentions of professionals and the expectations of users. For this, the theoretical and methodological framework of Alfred Schütz's Social Phenomenology was used. Thus, this is a phenomenological study, in the light of Alfred Schütz's Social Phenomenology, on the reciprocity of perspectives of professionals and users of a Psychosocial Care Center. It occurred in a Psychosocial Care Center for Alcohol and Other Drugs in a municipality in the northern region of the State of Rio Grande do Sul, Brazil. For its development, Resolution nº 466/12 was observed. Initially, the approach and setting in the research scenario took place in March 2023. Subsequently, data production began using phenomenological interviews, individually, from April to August 2023. 13 participants participated health professionals and 13 users of the Psychosocial Care Center for Alcohol and Other Drugs. To analyze the data, the steps mentioned and suggested by Social Phenomenology researchers were used. The intersubjective relationship established between health professionals and users of the Alcohol and Other Drugs Psychosocial Care Center revealed the typical actions of the Singular Therapeutic Project in this scenario. And, through the analysis of the professionals' intentionality and the users' expectations, it was possible to understand the reciprocity of perspectives regarding the actions of the Singular Therapeutic Project developed by the professionals. Thus, through a comprehensive analysis of what was experienced, it was learned that professionals and users share the perception of most of the actions of the Singular Therapeutic Project, except: team meetings; and co-responsibility/autonomy in treatment. It was revealed that the intentions of professionals and the expectations of users regarding the actions of the Singular Therapeutic Project converge only with regard to rehabilitation/social reintegration. Social Phenomenology contributed to the identification of the actions of the Singular Therapeutic Project developed by professionals who work in mental health, more specifically, in alcohol and other drug policies. As a theoretical and methodological reference, it makes it possible to contour the hegemonic and asylum care model in mental health. Furthermore, it is believed that the research contributed to the identification of challenges and potential faced by health professionals and users of psychoactive substances, in the context of the Psychosocial Care Center for Alcohol and Other Drugs.